2021
DOI: 10.2186/jpr.jpor_2019_436
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic performance of one-piece and two-piece implant:a systematic review and meta-analysis

Abstract: The aim of this system review was to evaluate clinical and radiographic performance of one-piece implant (OPI) and two-piece implant (TPI). Methods: Electronic database searches were performed in MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and OpenGrey databases up to May 2019. Two authors individually screened the related literatures according to the inclusion and exclusion criteria. Main clinical outcomes included failure and complication rates. Radiographic outcomes were peri-implant bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This can be explained in the fact of the strong one body design and the improved mechanical properties for the one piece implant compared to the two piece one. The absence of the abutment screw contributes to such improved mechanical properties in the one-piece implant as well [ 14 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained in the fact of the strong one body design and the improved mechanical properties for the one piece implant compared to the two piece one. The absence of the abutment screw contributes to such improved mechanical properties in the one-piece implant as well [ 14 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Vorous et al [ 16 ] stated non significant difference in their systematic review between both implant types regarding the level of marginal bone loss. Furthermore, Liu et al [ 17 ] concluded in their subgroup meta analysis that the two piece dental implants with platform switching had a significant reduced level of marginal bone loss compared to the one piece ones.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has to be mentioned that the stress level is not the only factor that affects marginal bone loss since further factors as the design of the implant platform, presence of cantilevers, occlusal forces in addition to the implant number and diameter have their effect too [40]. Moreover, systematic reviews dealing with the issue of marginal bone loss in the one piece and two piece dental implants reported controversial results and concluded that both implant types showed no difference in their effect on marginal bone loss [16,17]. However, such results should be held with caution due to the possible heterogeneity of the studies enrolled in the systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Vorous et al stated non signi cant difference in their systematic review between both implant types regarding the level of marginal bone loss [16]. Furthermore, Liu et al concluded in their subgroup meta analysis that the two piece dental implants with platform switching had a signi cant reduced level of marginal bone loss compared to the one piece ones [17].…”
Section: Introductionmentioning
confidence: 99%
“…16 The unique design of this implant provides several advantages such as high mechanical strength, more simple surgical technique, no microgap between implant and abutment, and similar to the conventional crown and bridge procedures. 20 Retention of the superstructure to one-piece implant depends on several factors, such as implant form, cement type and surface treatments. [21][22][23] As zirconia has high strength, 8 it can be bonded using zinc phosphate cement, glass ionomer cement or resin modified glass ionomer cement.…”
Section: Introductionmentioning
confidence: 99%